Quality assurance at The University of the West Indies - Gift, Sandra (2010)
Presents an overview of the quality assurance model at the University of the West Indies. Discusses the intended and actual outcomes of the model focussing on the impact of programme review on the quality of teaching and learning, and identifies wise practices across the three residential campuses. Reflects on the successes, constraints and challenges.